LEGAL REVIEW OF PTUN DECISION NO. 87/G/2014/PTUN-JKT RELATED TO THE DISPUTE OVER THE DISMISSAL OF STUDENTS BY THE UNIVERSITY - Sirait, Timbo Mangaranap; Khalimi; Naiborhu, Mesa Indra (JILPR Journal Indonesia Law and Policy Review, 2025)
Agent of change is one of the roles given to students, but sometimes in the process they experience obstacles until they are finally dismissed by the Chancellor, so that the decision needs to be analyzed from the perspective of state administrative and constitutional law. The research was conducted using the Normative Juridical Method through literature study and case analysis of PTUN Decision No. 87/G/2014/PTUN-JKT. The problems discussed are: (1) whether the decision is a beschikking that can be used as an object of dispute at the PTUN, and (2) how the constitutional basis strengthens the jurisdiction of the PTUN in this case. The results of the study show, First, that the rector's action fulfills the elements of a State Administrative Decision (Beschikking) and is thus valid as an object of lawsuit. Second, the jurisdiction of the State Administrative Court in the dispute is strengthened not only from the juridical aspect, but also from the principle of due process of law, the values of Pancasila, and the guarantee of the right to education in the constitution, thus recommending the need for caution of university officials in making administrative decisions to remain in line with the principle of substantive justice.